Self-purging pyrolysis of sugarcane bagasse biomass to highly order microporous biochar production - Mohamed Noor, Noraini; Abdullah, Ezzat Chan (2018)
In this study, biochar was produced from sugarcane bagasse in a modified muffle furnace without using a purging gas at different temperatures; 400˚C to 700˚C with increments of 50˚C at 25˚C/min heating rate. Biochar yields were significantly influenced by the devolatization of biomass during the pyrolysis and were inversely proportional to the temperature. The holding time was also found to have a significant effect on biochar yields. The maximum biochar yields from sugarcane bagasse, at 10, 20 and 30 minutes holding times, were 27.11, 26.35, and 28.48%, respectively. The highest biochar yield at different holding times was obtained at a temperature of 400°C. The physicochemical properties of biomass and biochar were analysed. The results obtained from characterization showed that SCBC30 showed the highest BET surface area of 348.12 m 2 /g. From the FTIR results, SCBC10 showed fewer peaks, which indicated a smaller presence of functional groups than SCB-BC20 and SCB-BC30 due to an incomplete transformation of raw SCB wastes to biochar.